The role of late Quaternary tectonic activity and sea-level changes on sedimentary processes interaction in the Gulf of Cadiz upper and middle continental slope (SW Iberia). (November 2020) - García, M.; Llave, E.; Hernández-Molina, F.J.; Lobo, F.J.; Ercilla, G.; Alonso, B.; Casas, D.; Mena, A.; Fernández-Salas, L.M.
Abstract: A morphological and seismic-stratigraphic analysis of the Gulf of Cadiz area near the Strait of Gibraltar is presented in this work, focused on the sedimentary evolution of the upper and proximal middle-continental slope since the Mid-Pleistocene. Based on the analysis of seismic reflection profiles and swath bathymetry data, this work analyses the close influence of the activity of buried and outcropping diapiric ridges and late Quaternary sea-level changes on the evolution of contouritic features related to the Mediterranean Outflow Water (MOW) and Eastern North Atlantic Central Water (ENACW), gravitational features and fluid-escape structures. The stratigraphic architecture reveals that, under active diapiric deformation, the upper slope plastered drift grew during low sea-level stages, when sediment supply was high and the ENACW swept the upper slope, contrasting with the present-day highstand situation dominated by northwest-trending MOW flow. The south-estward ENACW flow forced asymmetry and lateral migration of gullies incised in the plastered drift. Two evolutionary stages have been established: 1) After the Mid Pleistocene, activity of diapirs with a NE trend determined the location of the deepest depressions which were infilled by plastered contouritic drifts; 2) Between Late Quaternary and present, a drastic change of buried diapirs growth pattern and orientation to a NW trend enhanced slope-derived gravitational processes affecting the bottom current dynamics. Adjustments to tectonic changes led to a phase of plastered drift growth on the upper slope during which depocenters varied their distribution and orientation. In a long-term the structural control on sedimentation shows a northwestward displacement of deformation, resulting in an overall extension of the contourite depositional system to the NW. In a short-term, sea-level changes favored drift deposition, gullies incision and the strengthening of water masses. This work evidences the importance of tectonic deformation in sedimentation at recent time scales, and the two-directional interplay between recent tectonic activity and bottom current dynamics. Highlights: We show diapiric activity and sea-level control on sedimentation in the Gulf of Cadiz. A plastered drift was deposited during lowstands on the ENACW-affected upper slope. A contourite channel was incised in the proximal middle slope by the MOW. Since the Late Quaternary diapiric activity changed its trend and migrated to the NW. Sedimentary processes adapted to the margin morphology created by diapir activity.